2020
DOI: 10.30843/nzpp.2020.73.11717
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Ceratocystis fimbriata from New Zealand kūmara on kiwifruit cultivars

Abstract: INTRODUCTION Ceratocystis fimbriata is a fungal pathogen that affects a wide variety of plant hosts, in more than 22 families, many of which are of commercial importance. It was first identified on Ipomoea batatas in northeastern USA in 1890 (Halsted 1890), and since then has been widely reported across the world. Ipomoea batatas is known as kūmara in New Zealand and as sweet potato in many other parts of the world, and this distinction is used here. The first record of C. fimbriata in New Zealand was by Kirk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…For instance, C. fimbriata has been reported on taro, sweet potato, pomegranate, eucalyptus, and mango in Yunnan Province in China, one of the kiwifruit-growing areas and also where the Actinidia Biodiversity Centre is located (Huang, 2016), representing a serious threat to one of the greatest kiwifruit germplasm collections in the world. In New Zealand C. fimbriata has been reported on sweet potato, but the strain found in that area is not able to infect kiwifruit (Tyson et al, 2020).…”
Section: F I G U R Ementioning
confidence: 98%
“…For instance, C. fimbriata has been reported on taro, sweet potato, pomegranate, eucalyptus, and mango in Yunnan Province in China, one of the kiwifruit-growing areas and also where the Actinidia Biodiversity Centre is located (Huang, 2016), representing a serious threat to one of the greatest kiwifruit germplasm collections in the world. In New Zealand C. fimbriata has been reported on sweet potato, but the strain found in that area is not able to infect kiwifruit (Tyson et al, 2020).…”
Section: F I G U R Ementioning
confidence: 98%
“…The intraspeci c and interspeci c variability in the Ceratocystis species is related to host speciation, aggressiveness variation, and speci c interactions with certain cultivars or clones (Cowger et al, 2000;Oliveira et al, 2020). Some species and/or isolates are related to single hosts or geographic regions, while others infect a wide range of hosts (Thorpe et al, 2005;Tyson et al, 2020). Since the rst report of Ceratocystis wilt on kiwifruit vines (Sonego et al, 2010), investigation of pathogenicity of Ceratocystis spp.…”
Section: Full Textmentioning
confidence: 99%
“…found in other countries, mainly those occurring in kiwifruit-producing countries, has become important for implementing biosecurity measures to prevent the introduction of pathogenic isolates in kiwifruit orchards. Tyson et al (2020) showed that New Zealand isolates of C. mbriata from sweet potato (kumara) are not pathogenic to a range of kiwifruit cultivars (Hayward, Gold3, Gold14, Bounty). In addition, the sweet potato isolates were non-pathogenic on mango (Mangifera indica), yam (Dioscoera spp.…”
Section: Full Textmentioning
confidence: 99%
“…The complex Ceratocystis fimbriata sensu lato (s.l.) is formed by a group of species with a high genetic variability, with some species or isolates related to single hosts or geographic regions, while others infect a wide range of hosts (THORPE et al, 2005;TYSON et al, 2020). Furthermore, the C. fimbriata intraspecific variability is related to aggressiveness variation and specific interaction may occur with particular cultivar or clone (COWGER et al, 2000;.…”
Section: General Introductionmentioning
confidence: 99%
“…The complex Ceratocystis fimbriata sensu lato (s.l.) is formed by a group of very similar fungi and with a high number of isolates widely distributed geographically, some species are related to single hosts or geographic regions, while others infect a range of hosts (Thorpe et al 2004, Tyson et al 2020. The wide host range of C. fimbriata (s.l.)…”
Section: Introductionmentioning
confidence: 99%